Smaller total and subregional cerebellar volumes in posttraumatic stress disorder: a mega-analysis by the ENIGMA-PGC PTSD workgroup - Huggins, Ashley A; Baird, C Lexi; Briggs, Melvin; Laskowitz, Sarah; Hussain, Ahmed; Fouda, Samar; Haswell, Courtney; Sun, Delin; Salminen, Lauren E; Jahanshad, Neda; Thomopoulos, Sophia I; Veltman, Dick J; et al. (Molecular psychiatry, 2024)
Although the cerebellum contributes to higher-order cognitive and emotional functions relevant to posttraumatic stress disorder (PTSD), prior research on cerebellar volume in PTSD is scant, particularly when considering subregions that differentially map on to motor, cognitive, and affective functions. In a sample of 4215 adults (PTSD n = 1642; Control n = 2573) across 40 sites from the ENIGMA-PGC PTSD working group, we employed a new state-of-the-art deep-learning based approach for automatic cerebellar parcellation to obtain volumetric estimates for the total cerebellum and 28 subregions. Linear mixed effects models controlling for age, gender, intracranial volume, and site were used to compare cerebellum volumes in PTSD compared to healthy controls (88% trauma-exposed). PTSD was associated with significant grey and white matter reductions of the cerebellum. Compared to controls, people with PTSD demonstrated smaller total cerebellum volume, as well as reduced volume in subregions primarily within the posterior lobe (lobule VIIB, crus II), vermis (VI, VIII), flocculonodular lobe (lobule X), and corpus medullare (all p-FDR < 0.05). Effects of PTSD on volume were consistent, and generally more robust, when examining symptom severity rather than diagnostic status. These findings implicate regionally specific cerebellar volumetric differences in the pathophysiology of PTSD. The cerebellum appears to play an important role in higher-order cognitive and emotional processes, far beyond its historical association with vestibulomotor function. Further examination of the cerebellum in trauma-related psychopathology will help to clarify how cerebellar structure and function may disrupt cognitive and affective processes at the center of translational models for PTSD.
Keywords: Cerebellum; mozeček; bílá hmota; Middle Aged; mužské pohlaví; Gray Matter; Adult; magnetická rezonanční tomografie; Organ Size; velikost orgánu; Magnetic Resonance Imaging; Deep Learning; ženské pohlaví; šedá hmota; Humans; Stress Disorders, Post-Traumatic; lidé středního věku; posttraumatická stresová porucha; White Matter; dospělí; deep learning; Female; lidé; Male